Faktor-Faktor yang Berhubungan dengan Kejadian Anemia pada Ibu Hamil - Neshy Sulung; Najmah Najmah; Rostika Flora; Nurlaili Nurlaili; Samwilson Slamet (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the factors associated with anemia in pregnant women. The method used in this study is a descriptive-analytic study with a cross-sectional design. The results showed that most of the respondents (50.5%) were highly educated; 75.2% work as housewives; 74.2% have good nutritional status; 78.9% were irregular in taking blood supplement tablets; 84.4% had anemia. The bivariate analysis results showed that education, nutritional status, occupation, and regularity obtained p-values of 0.12; 0.22; 0.03; and 0.008. In conclusion, there is a relationship between work and regular consumption of blood-added tablets with anemia in pregnant women. Keywords: Anemia, Factors, Pregnant Women